2D CALCULATIONS OF COLLAPSE OF ROTATING MAGNETIZED BODIES - Ardeljan, N. V.; Bisnovatyi-Kogan, G. S.; Moiseenko, S. G. (Одеські астрономічні публікації, 2017)
2D numerical simulation of the collapse of rotating magnetized cloud has been made as preliminary investigation of magnetorotational mechanism of supernova explosion. The part of envelope of the cloud is throwing out when magnetic pressure becomes comparable with gas pressure. The amount of mass of the envelope thrown out and the energy it carries away are estimated.